2012
DOI: 10.2174/092986712801215900
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Kits for Hexosamine Biosynthetic Pathway in Oncology

Abstract: Noninvasive imaging assessment of tumor cell proliferation could be helpful in the evaluation of tumor growth potential, the degree of malignancy, and could provide an early assessment of treatment response prior to changes in tumor size determined by computed tomography (CT), magnetic resonance imaging (MRI), Positron emission tomography (PET), Single-Photon emission computed tomography (SPECT) or ultrasonography, respectfully. Understanding of tumor proliferative activity, in turn, could aid in the selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Glucosamine, although normally present at low levels in bodily fluids, enters into cells via the glucose transporters (16) and is phosphorylated to glucosamine-6-phosphate by hexokinase, thereby bypassing GFAT and elevating UDP-GlcNAc levels. Recently, Yang et al demonstrated that radiolabeled glucosamine analogs can be introduced as novel agents to complement FDG imaging to increase specificity and improve the accuracy of lesion size in oncology applications (17). Glucosamine analogs become UDP-GlcNAc analogs and the newly modified O -GlcNAc analog proteins catalyzed by OGT are found in the cytoplasm and nucleus, whereas FDG, a glucose analog, is not metabolized and remains in the cytoplasm of cells.…”
Section: Hbp Metabolic Shifts and Cancermentioning
confidence: 99%
“…Glucosamine, although normally present at low levels in bodily fluids, enters into cells via the glucose transporters (16) and is phosphorylated to glucosamine-6-phosphate by hexokinase, thereby bypassing GFAT and elevating UDP-GlcNAc levels. Recently, Yang et al demonstrated that radiolabeled glucosamine analogs can be introduced as novel agents to complement FDG imaging to increase specificity and improve the accuracy of lesion size in oncology applications (17). Glucosamine analogs become UDP-GlcNAc analogs and the newly modified O -GlcNAc analog proteins catalyzed by OGT are found in the cytoplasm and nucleus, whereas FDG, a glucose analog, is not metabolized and remains in the cytoplasm of cells.…”
Section: Hbp Metabolic Shifts and Cancermentioning
confidence: 99%
“…Clinical studies revealed that 99m Tc-EC-G was safe and had favorable radiation dosimetry in NSCLC patients ( 104 ). 99m Tc-EC-G was able to distinguish tumor from inflammation due to its downstream post-transcriptional HBP with DNA proliferation ( 104 108 ) ( Figure 5 ). 99m Tc-EC-G was not inferior to FDG for imaging in patients with NSCLC ( 102 ).…”
Section: Modulators Of Radiation-induced Pulmonary Toxicitiesmentioning
confidence: 99%
“…Skill in interpretation is therefore required to minimise the possibility of false positive and negative results. Some of these drawbacks of 18-F FDG may be minimised by the novel radiolabeled glucosamine analogues now becoming available, which can achieve a greater degree of specifi city for malignant tumours, targeting the hexosamine biosynthetic pathway rather than the glycolytic pathway (Yang et al , 2012 ). In the meantime, the effectiveness and versatility of 18-F FDG, helped by continued refi nements to current imaging protocols, will maintain its undisputed position as the most important PET tracer for some years to come.…”
Section: Fluoride Fl Uorodeoxy-d-glucose (Fdg)mentioning
confidence: 99%